2023
DOI: 10.1111/ijlh.14119
|View full text |Cite
|
Sign up to set email alerts
|

White blood cell differentials performance of a new automated digital cell morphology analyzer: Mindray MC‐80

Abstract: IntroductionThe manual differential count has been recognized for its disadvantages, including large interobserver variability and labor intensiveness. In this light, automated digital cell morphology analyzers have been increasingly adopted in hematology laboratories for their robustness and convenience. This study aims to evaluate the white blood cell differential performance of the Mindray MC‐80, the new automated digital cell morphology analyzer.MethodsThe cell identification performance of Mindray MC‐80 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
(66 reference statements)
1
3
0
Order By: Relevance
“…In this context, we have demonstrated the MC‐80's commendable performance in accurately pre‐classifying blasts in patients, exhibiting high sensitivity (92.0%). Our results are in line with several previously reported studies 11,14 . A notable advancement of the MC‐80 is its application of the deep convolutional neural network (CNN) model, which represents an improvement over previous technologies.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this context, we have demonstrated the MC‐80's commendable performance in accurately pre‐classifying blasts in patients, exhibiting high sensitivity (92.0%). Our results are in line with several previously reported studies 11,14 . A notable advancement of the MC‐80 is its application of the deep convolutional neural network (CNN) model, which represents an improvement over previous technologies.…”
Section: Discussionsupporting
confidence: 92%
“…10 As a DM analyzer launched in China, the MC-80 has exhibited excellent performance in leukocyte morphology analysis, as indicated by several independent studies. 11,12 There is a growing trend in comparing the performance of different brands of DM analyzers, such as CellaVision DC-1 versus Sysmex DI-60, 13 Mindray MC-80 versus Cel-laVision DM 9600, 14 and Mindray MC-100i versus Sysmex DI-60. 15 CellaVision has developed a series of automated morphological analysis systems, including the DM96, DM1200, and DM 9600.…”
Section: Introductionmentioning
confidence: 99%
“…This could increase work efficiency in blood cell morphology observing. 21,22 This study shows significant differences in erythrocyte morphology between TT and control groups. The percentages of many abnormal erythrocytes in the TT group were significantly higher than those in the control group.…”
Section: Discussionmentioning
confidence: 67%
“…The application of digital morphology (DM) analyzers has been increasing in the clinical practice for the peripheral blood smear (PBS) examination [ 1 , 2 , 3 , 4 ]. Numerous studies have reported that DM analyzers may show reliable performances for white blood cell (WBC) counts and differentials after verification [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. DM analyzers are also expected to reduce the workloads and turnaround times (TAT) of PBS examinations in clinical laboratories [ 5 , 9 , 10 , 11 , 13 ].…”
Section: Introductionmentioning
confidence: 99%